IMPROVEMENT OF BUS OPERATIONAL CHARACTERISTICS WHILE USING INTEGRATED CONTROL OF SUSPENSION AND TRANSMISSION - V. V. Mikhailau; A. G. Snitkov; S. V. Liahov (Наука и техника)
Semi-natural tests for active pneumatic suspension of a 18-tonne tourist bus with the system of automatic body stabilization of the mobile machine and feed-back coupling according to kinematics parameter. The test have been executed in the cases when the bus is stocked with an automatic hydro-mechanical transmission in the process of speed picking up, gear-changing or road braking which is assigned by accidental road humps. A computer simulation of dynamic structures in combination with virtual devices and real objects (HIL – Hardware-in-the-Loop Simulation) has been carried in the paper. Personal computers, software, programmed logic controller, frequency generator, solenoid-operated valve have been used for the investigation process. The paper proposes an unconventional method for improvement operational characteristics which is based on integrated control of a suspension and automatic hydro-mechanical transmission. A mathematical model includes systems of automatic transmission, suspension and module for generation of accidental road humps. The model has been considered as a basis for semi-natural laboratory bench with industrially-manufactured controller, other components of automatic systems and standard control organs. The most efficient method for body stabilization is control of the suspension according to the parameter of angular rate during vertical turn of an automobile’s center line with a turning point in the center of mass. The developed algorithm and stabilization system according to angular rate of body’s center line turning have made it possible to improve dynamics of the bus while making gear-changing and to reduce fuel consumption during starting-up and speed picking-up processes. During the braking process such system simultaneously decreases oscillation amplitude of some parameters more than two-fold.